Legal regulation of consumer rights: the best world practices in historical retrospective - Burashov, Sh.U.; Keskin, D. (Bulletin of the Karaganda University “Law Series”, 2022)
Effective legislation and successful law enforcement practice of consumer protection in developed countries is the best model for receiving into the national law of those states in which there is a need to modernize con-sumer legal relations. In this study, to create an objective global paradigm of consumer protection, a sample of countries with different efficiency levels of legal regulation is considered. Under the global trends in the development of legal regulation of consumer protection, a conclusion was made on the globalization of the consumer movement based on international legal standards. It is proved that the evolution of the development of national law of modern states is due to the tendencies of the UN and regional organizations in the regula-tion of consumer legal relations. As consumers of the European Union member states belong to the category of the most protected consumers, the conclusion is substantiated on the effectiveness of the mechanisms of dual regulation of consumer legal relations – at the level of European/communitarian and national law of the member states of this regional organization. A retrospective analysis of the global evolution of the institution of consumer protection is summarized by the classification of levels of consumer protection (individual, busi-ness, public, state, international). The analysis of the world practice of consumer rights protection substantiat-ed the conclusion that a multifaceted system of models of legal protection has been formed in the modern world: Judicial, state, public, local government bodies.